The boundaries of the surgical treatment of locally advanced and metastatic renal cell cancer (mRCC) – do they exist and how they are changing? - Borkowski, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2007)
Before the immunotherapy era the results of surgical treatment of mRCC were bad. 53% of patients survived 6 months, 43% 1 year, 26% 2 years and 13% 5 years. Favourable factors influencing the survival rate were: lung metastases only, absence of local recurrence or residual tumour, and a long period between kidney removal and appearance of metastases. Single long-term survivals justified these sometimes heroic surgical procedures; however, in many centres patients with central nervous system metastases, bone metastases and/or liver metastases were disqualified from surgery. Therapy of bone metastases helped to control pain and prevented pathological fractures. After combining nephrectomy with immunotherapy the results were better than after immunotherapy alone or nephrectomy alone. This changed everyday practice. In many centres nephrectomy was always performed when technically feasible and patients were referred to oncology centres for further immunotherapy or chemoimmunotherapy. This situation changed radically when new oncological drugs such as thyrosine kinase inhibitors (sunitinib, sorafenib), mTOR inhibitors (temisirolimus) or VEGF monoclonal antibodies were introduced. The high percentage of patients with progression-free survival made questionable the role of nephrectomy in new treatment schemes. The explanation of this problem and establishment of the surgical therapy role in mRCC will only be possible after a series of prospective clinical trials which are about to begin.